Graphene Oxide Surface Treatment on Piassava Fiber Attalea funifera to Improve Adhesion in Epoxy Matrix. Issue 14 (28th October 2022) - Luz, Fernanda Santos da; Garcia Filho, Fabio da Costa; Costa, Ulisses Oliveira; Oliveira, Michelle Souza; Monteiro, Sergio Neves
ABSTRACT: The growing environmental awareness in the last few decades has driven the research and development of composites reinforced with natural fibers as an alternative to replace synthetic fiber composites. However, their hydrophilic character and surface heterogeneity may be considered a challenge to allow reliable and wide application of these materials. One way to overcome this drawback is the modification of the surface of the fiber by chemical and/or physical treatments. Among these treatments, the graphene oxide (GO) has stood out due to its amphiphilic character. In the present work, the influence of GO-treatment in piassava fiber was investigated. The interfacial adhesion between the piassava fiber, both untreated and with GO, and the epoxy resin was evaluated by pullout tests. Fourier transform infrared spectroscopy (FTIR) and Raman spectroscopy were also performed to verify the effectiveness of the GO-treatment on the piassava fiber. The fiber's surface morphology was further investigated by scanning electron microscopy (SEM). The GO-treatment of the piassava fiber enhanced the interfacial shear strength by ∼171% more than untreated fibers. This could allow new applications of these eco-friendly composites as high-performance materials.